Epitranscriptomic signatures in blood: emerging biomarkers for diagnosis of diabetes and its complications - Hlavackova, Marketa; Benak, Daniel; Holzerova, Kristyna; Alanova, Petra; Hrdlicka, Jaroslav; Chalupova, Miloslava; Opletalova, Barbora; Ostadal, Bohuslav; Kolar, Frantisek (Frontiers in Cell and Developmental Biology, 2025)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder characterized by chronic hyperglycemia, insulin resistance, and progressive β-cell dysfunction. Traditional biomarkers, such as fasting glucose and glycated hemoglobin (HbA1c), offer diagnostic and prognostic value but have limitations in sensitivity and predictive power for disease progression. Recent advances in molecular biology have identified epitranscriptomic modifications as potential biomarkers for T2DM, offering a novel layer of gene expression regulation through reversible RNA modifications. Dysregulation of these modifications has been implicated in insulin resistance, β-cell failure, and diabetes-related complications. Notably, altered levels of N6-methyladenosine (m6A) and its regulatory enzymes, including the eraser fat mass and obesity-associated protein (FTO) and the writer methyltransferase-like 3 (METTL3), have been detected in peripheral blood of T2DM patients, suggesting their potential as promising diagnostic markers. Similarly, circulating levels of pseudouridine (Ψ) have been associated with diabetic complications such as retinopathy and nephropathy. This review highlights the emerging role of epitranscriptomic modifications in T2DM pathophysiology and discusses their translational potential as biomarkers for early detection, disease monitoring, and personalized therapeutic strategies.